What questions about patient care do physicians have during and after patient contact in the ED? The taxonomy of gaps in physician knowledge. Issue 10 (27th September 2007) - Graber, Mark A; Randles, Bradley D; Monahan, Jay; Ely, John W; Jennissen, Charles; Peters, Bobby; Anderson, Dean
Abstract : Objectives: To categorise questions that emergency department physicians have during patient encounters. Methods: An observational study of 26 physicians at two institutions. All physicians were followed for at least two shifts. All questions that arose during patient care were recorded verbatim. These questions were then categorised using a taxonomy of clinical questions. Results: Physicians had 271 questions in the course of the study. The most common questions were about drug dosing (35), what drug to use in a particular case (28), "what are the manifestations of disease X" (23), and what laboratory test to do in a situation (21). Notably lacking were questions about medication costs, administrative questions, questions about services in the community, and pathophysiology questions. Conclusions: Emergency department physicians tend to have questions that cluster around practical issues such as diagnosis and treatment. In routine practice they have fewer epidemiologic, pathophysiologic, administrative, and community services questions.